2023
DOI: 10.1002/mp.16240
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Energy dependence of the Gafchromic EBT4 film: Dose‐response curves for 70 kV, 6 MV, 6 MV FFF, 10 MV FFF, and 15 MV x‐ray beams

Abstract: Background: EBT4 was newly released for radiotherapy quality assurance to improve the signal-to-noise ratio in radiochromic film dosimetry. It is important to know its dose-response characteristics before its use in the clinic. Purpose: This study aims to investigate and compare the dose-response curves of the Gafchromic EBT4 film for megavoltage and kilovoltage x-ray beams with different dose levels, scanning spatial resolutions, and sizes of region of interest (ROI). Methods: EBT4 film (Lot#07052201) calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…A recent study on the new EBT4 film has reported high‐energy photon beams of nearly independent energy (6 MV, 6 MV Flattening‐Filter‐Free [FFF], 10 MV FFF, and 15 MV) were used in radiotherapy. However, for low‐energy photons (70 kV), there is an energy dependence, with a difference of up to 12% 25 . Several studies have studied characteristics of the Gafchromic EBT film series and scanning procedures, including energy dependence, 4,6,22 absorption spectra, 10 film homogeneity, 11 temperature dependence, 8,12 ambient light sensitivity, 12 post‐exposure coloration, 4,6,12 and variations among different lot numbers 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on the new EBT4 film has reported high‐energy photon beams of nearly independent energy (6 MV, 6 MV Flattening‐Filter‐Free [FFF], 10 MV FFF, and 15 MV) were used in radiotherapy. However, for low‐energy photons (70 kV), there is an energy dependence, with a difference of up to 12% 25 . Several studies have studied characteristics of the Gafchromic EBT film series and scanning procedures, including energy dependence, 4,6,22 absorption spectra, 10 film homogeneity, 11 temperature dependence, 8,12 ambient light sensitivity, 12 post‐exposure coloration, 4,6,12 and variations among different lot numbers 13 …”
Section: Introductionmentioning
confidence: 99%
“…However, for low-energy photons (70 kV), there is an energy dependence, with a difference of up to 12%. 25 Several studies have studied characteristics of the Gafchromic EBT film series and scanning procedures, including energy dependence, 4,6,22 absorption spectra, 10 film homogeneity, 11 temperature dependence, 8,12 ambient light sensitivity, 12 post-exposure coloration, 4,6,12 and variations among different lot numbers. 13 EBT3 films exhibit two types of geometrical effects: scanning orientation 4,6,12,16,17,20 and lateral response artifact (LRA) 5,7,[15][16][17][18][19][20][21][22] effects.…”
Section: Introductionmentioning
confidence: 99%
“…The flattening-filter-free (FFF) beams were not selected for the film characterization in our study because using the non-uniform dose profile of a FFF beam is likely to introduce large inaccuracy in the quantitative analysis if the radiation field center on the film image is not identified accurately. The characterization of EBT4 film using FFF beams can be found in the report by Chan et al 2 For electron irradiations, 6, 12, and 20 MeV beams were selected, representing low, medium, and high clinical electron energies. In the irradiation, the gantry was rotated to 0 • with a standard setup: source-to-surface distance (SSD) = 100 cm, and field size = 10 × 10 cm 2 in the isocenter plane.…”
Section: Experimental Setup For MV Photon and Mev Electron Beams Usin...mentioning
confidence: 99%
“…There are four fitting coefficients in this function, as defined in Equation (2), where x is the gray value or net OD, y is dose, and a, b, c and d are fitting coefficients. 6 In the present study, only the net OD was used in the film calibration.…”
Section: Film Image Analysismentioning
confidence: 99%
“…Radiochromic films, such as EBT3 film or EBT4 film, are suitable candidates for PRDR dosimetry due to their energy independence, angular independence, high spatial resolution, and 2D readout 15–17 . Several investigations have previously evaluated the dose rate dependence of radiochromic films for conventional dose rates above 100 MU/min 15,18–21 .…”
Section: Introductionmentioning
confidence: 99%